CRITICAL REVIEW ON MADHU W.S.R. TO HONEY - Khemchand, *Sharma; Chinky, Goyal; Deepchand, Prajapati (International Journal of Ayurveda and Pharma Research, 2015)
Honey is a natural sweet substance produced by honey bees and is one of the most valued as well as appreciated natural substance known to mankind since ancient times. Of all the natural foods rich in carbohydrates honey is the most wholesome and delicious. The medicinal quality, taste, texture, color and aroma of honey differs according to the geographical area and the species of plants from which it has been collected. Honey is called as Madhu in Ayurveda. Eight types of Madhu are described in Ayurveda depending on the type of bee which collects it and `Makshika is considered medicinally the best among them. According to biomedical science, the best honey is made by Apis mellifera. Etymology, Synonyms, varieties, method of collection, chemical constituents, properties, adulterants, chemical tests, and the usages of honey are gathered from text books, experienced Ayurvedic physicians and from internet. In Ayurveda, honey is used for both internal and external applications.  It shows mild laxative, bactericidal, sedative, and antiseptic properties and is found to be useful in the treatment of bronchial asthma, tuberculosis, cough and cold, eye diseases, wounds, constipation, hiccups, skin disorders, worm infestation and urinary tract disorders etc. Old honey reduces fat and obesity and is highly scarificant. Honey is much used in the preparation of confections and electuaries and as an adjunct to decoctions, pills and powders. But problem of its adulteration is becoming a common issue in present scenario, so it is always necessary to use genuine honey for attaining desired benefits and reject the spurious and adulterated honey which is sold cheaper in the market. The present work aims at the review of Honey or Madhu as is explained in Ayurveda & biomedical science.